Determination of Overall Equipment Efectiveness Superflex Machine Using Fuzzy Approach - Santosa, Sesar Husen; Irawan, Suhendi; Ardani, Ilham (International Journal of Artificial Intelligence Research, 2020)
This study aimed to present a Fuzzy logic approach in determining the value of OEE Superflex machine for producing nuggets. The effectiveness value of Superflex machine in producing nugget raw materials was determined by calculating the Availability, Performance and Quality Yield values. Fuzzy approach in determining the value of OEE can be used because this approach is able to describe the value of the effectiveness of thr machines based on the condition of the company's actual capacities. The Fuzzy OEE approach uses the Trapezoidal Membership Association because the maximum value of the membership degree has more than one value in each parameter. The Fuzzy OEE value shows that Superflex machine had an OEE value with bad parameters so that the company has to improve its machine performance